Pelaksanaan Literasi Al-Qur`An dalam Menanamkan Budaya Religius di UPTD SMP 7 - Suriyati, Suriyati; Ramadani, Nuriya (J-SES : Journal of Science, Education and Studies, 2024)
Al-Qur`an literacy is a very crucial thing that must be instilled in every Muslim, especially the younger generation. Al-Qur`an literacy can be implemented in various activities, both at school, in the community and in the family environment. With this, the researcher the theme of impementing al-qur`an literacy in instilling religious culture in schools, namely UPTD SMPN 7. The aim of this research is to determine the preservation of religious culture through implementing al-qur`an literacy. The approach method used in this research isdescriptive-qualitative and uses data collection technique, namely observation interviews and literature. From the results of the literature study, it was found that al-qur`an literacy is the activity of reading, writing and understanding the al-qur`an. This activity is very important to do, because it can foster a religious culture in students. Understanding the Koran will give birth to religious values, such as faith, piety, noble morals and love. These values will become the basis for students on how to behave and act in accordance with islamic teachings.